Assessing the Optimum Proportion of Outdoor Spaces of Educational Sites, College of Engineering in Erbil City as a Case Study - Almumar, Mohammed M. Saeed; Mzoori, Faris Ali Mustafa (Sulaimani Journal for Engineering Sciences, 2016)
Many of Outdoor spaces (OS)s in the local existing educational institutional sites are narrow or wide, of inefficient degree of enclosure (DOE) and of reduced performance. Optimum proportion of OS in this paper is one that can ensure efficient performance of both the surrounding buildings and the OS itself, and also ensure minimum consumption of land, energy and material. DOE of OS in previous literature is associated only to the proportion of OS itself, whereas (DOE) in this paper is associated to other parameters in addition to proportion. They are; pattern of object configuration, permeability of vision of enclosing surfaces, and ambient environment. This paper attempts to establish a relationship between the DOE with the mentioned parameters, and to determine the optimum proportions of campus OSs for various uses. The site of the college of engineering in Salahiddin University is chosen as a case study to measure and record paper parameters with the help of a checklist. DOE evaluation of OS as a perceived performance is measured by the users for these OSs within a questionnaire. Results of this paper deduced the design criteria of the pattern and proportion of the physical objects forming the OS, that are capable to ensure anthropomorphic, healthy, sparing land consumption, and expedient outdoor environment for future campus developments.
Keywords: degree of enclosure; performance; configuration; permeability; consumption of land; environment